Latin American Immigration Ethics - Reed-Sandoval, Amy; Díaz Cepeda, Luis Rubén (University of Arizona Press, 2022)
Following an extended period of near silence on the subject, many social and political philosophers are now treating immigration as a central theme of the discipline. For the first time, this edited volume brings together original works by prominent philosophers writing about immigration ethics from within a Latin American context.Without eschewing relevant conceptual resources derived from European and Anglo-American philosophies, the essays in this book emphasize Latin American and Latinx philosophies, decolonial and feminist theories, and Indigenous philosophies of Latin America, in the pursuit of an immigration ethics. The contributors explore the moral challenges of immigration that either arise within Latin America, or when Latin Americans and Latina/o/xs migrate to and reside within the United States. Uniquely, some chapters focus on south to south migration. Contributors also examine Latina/o/x experiences in the United States, addressing the lacuna of philosophical writing on migration, maternity, and childhood.Latin American Immigration Ethics advances philosophical conversations and debates about immigration by theorizing migration from the Latin American and Latinx context.ContributorsLuis Rubén Díaz Cepeda, Lori Gallegos, Margaret Griesse, Eduardo Mendieta, José Jorge Mendoza, Amos Nascimento, Carlos Pereda, Silvana Rabinovich, Amy Reed-Sandoval, Raúl Villarroel, Allison B. Wolf